Evidence for Endovascular Simulation Training: A Systematic Review. Issue 3 (March 2016) - See, K.W.M.; Chui, K.H.; Chan, W.H.; Wong, K.C.; Chan, Y.C.
Abstract : Background: Simulation training in endovascular surgery provides opportunities for trainees to practice and learn from non-patient based experience. Several types of endovascular simulators are available commercially. Previous studies on endovascular simulation training can be categorized into trials in which only a simulator was used when measuring performance metrics or "trials within simulation"; patient specific procedure rehearsals; and randomized, controlled trials (RCTs) or translational studies. Objectives: To examine whether endovascular simulation training can improve surgeon techniques and patient outcomes in real clinical settings. Methods: A literature review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. All searches were done via PubMed and Embase. Review articles, and papers that were not related to endovascular surgery and not within the scope of interest were excluded. References of review articles were further screened according to the exclusion criteria. Results: In total, 909 records were identified and 290 duplicates were removed. Thirty-one were included in the qualitative analysis. Twenty-three were trials within simulation and most of them found statistically significant improvements in procedure time, fluoroscopy time, and contrast volume. Five were patient specific procedure rehearsals and showed that simulation significantly affected the fluoroscopy angle and improved performance metrics. Three were RCTs and revealed mainly positive results on a Global Rating Scale and procedure specific rating scale. Conclusions: Contemporary evidence shows that performance metrics within endovascular simulations improve with simulation training. Successful translation to in vivo situations is observed in patient specific procedure rehearsals and RCTs on real procedures. However, there is no level I evidence to show that predictive validity of simulation can definitively improve patient outcomes. Current literature supports the idea that there is a beneficial role of simulation in endovascular training. Future studies are needed to confirm the efficacy of simulation in endovascular surgical training and to see if simulation is superior to traditional training in the operating theatre.